Computer program to estimate genetic parameters from means and variances of experimental populations by the method of weighted least squares - de Toledo, José Francisco Ferraz (Pesquisa Agropecuaria Brasileira, 1991)
Estimating genetic parameters of important traits is a routine in most breeding programs. Estimates obtained by the weighted least square proceedings are nonbiased and efficient, but the actual estimating process may be cumbersome and time consuming. The calculations can and should be performed by a computer to improve the speed and the reliability of the whole process. This paper presents a computer program written in Fortran language that performs all the necessary calculations to estimate genetic parameters from means and variances of natural or experimental populations. The results are reliable and precise and the output includes statistics that evaluate the significance levels of the estimated parameters and the goodness-of-fit of the adjusted genetic model.